Thermal conductivity of synthetic boron-doped single-crystal HPHT diamond from 20 to 400 K. (28th March 2016) - Prikhodko, D.; Tarelkin, S.; Bormashov, V.; Golovanov, A.; Kuznetsov, M.; Teteruk, D.; Volkov, A.; Buga, S.
Abstract: Abstract : Thermal conductivity of single-crystal boron-doped diamond (BDD) was studied in comparison with high-quality pure IIa-type diamond in the temperature range from 20 to 400 K. Boron content in BDD was about 10 19 cm −3 that is a typical value of p+ substrates used for power device applications. The thermal conductivity of BDD is about 10 times less than that of IIa diamond near 100 K, but above room temperature the difference is <30%. The observed deviation mostly takes place due to acoustic phonon scattering on extended structural defects occurring in synthetic diamond at high boron content.